Worker’s Rights To Big Day In The Middle of Pandemic Covid 19 - Hari Adi Setyoko; Soemali (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Currently the earth is experiencing a Covid-19 pandemic. This pandemic has been rampant in all countries without exception Indonesia. It is undeniable that this pandemic has an impact on the world economy, especially Indonesia. As a result of this pandemic, many companies have gone, have been dismissed unilaterally in various companies, and there have also been those who did not cut ties unilaterally but did not provide rights to holiday allowances during this pandemic. Minister of Manpower, Ida Fauzia, said that there were 274 companies that were unable to pay the holiday allowance this year. This number is known from complaints that have been submitted to the post of complaint for holiday allowances at the Ministry of Manpower in the May period this year. The formulation of the problems contained in this study are: 1) Does every worker still have the right to get holiday allowances during the Covid-19 pandemic? 2) What are the legal remedies for workers who do not get the right to holiday allowances during the Covid-19 pandemic? The objectives of this study are: 1) To determine and analyze that every worker is still entitled to holiday allowances during the Covid-19 pandemic; 2) To find out and analyze legal remedies for workers who do not get the right to holiday allowances during the Covid-19 pandemic. The result of this research is that during the Covid-19 pandemic, workers must still have the right to holiday allowances as stated in the Circular of the Minister of Manpower No. M / 6 / HI.00.01 / V / 2020 concerning the Implementation of 2020 Religious Holidays Allowances in Companies During the Corona Virus Disease 2019 (Covid-19) Pandemic.